KEEFEKTIFAN MODEL PEMBELAJARAN TALKING STICK TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA DI SMP NEGERI 1 PINANGSORI - Hervinna Sriwati Sarumpaet (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
Abstract The aims of this study is to: 1) describe of using talking stick learning model, 2) describe effectiveness of using talking stick learning model, and 3) whether there is a significant influence of using talking stick learning model on students’ problem solving at the eighth grade students of SMP Negeri 1 Pinangsori. This research was conducted by applying experimental method with sample 38 students and they were taken by using cluster random sampling technique. Questionnaire and test were used in collecting the data. Based on descriptive analysis, it was found that: (1) the score of using talking stick learning model was 3.94 (very good category), (2) the effectiveness of using talking stick learning model was maximal because there was an increase in the average value Furthermore by using inferential statistic (Pair Sample ttest), it could be found tcalculated was less than 0.05 ( 0,000 <0.05). It means there is a significant influence of using talking stick learning model on students’ problem solving at the eighth grade students of SMP Negeri 1 Pinangsori.